2021
DOI: 10.3390/ma14195513
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Polymer-Infiltrated Ceramic Network with Biocompatible Adhesive to Potentiate Dental Implant Applications

Abstract: The aim of this work was to prepare and characterize polymer–ceramic composite material for dental applications, which must resist fracture and wear under extreme forces. It must also be compatible with the hostile environment of the oral cavity. The most common restorative and biocompatible copolymer, 2,2-bis(p-(2′-2-hydroxy-3′-methacryloxypropoxy)phenyl)propane and triethyleneglycol dimethacrylate, was combined with 3D-printed yttria-stabilized tetragonal zirconia scaffolds with a 50% infill. The proper scaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…They concluded that the investigated process allows for the free fabrication of high-performance components made of a ceramic matrix composite. A polymer–ceramic composite material for dental implant applications capable of withstanding high mechanical stress and wear was proposed and researched by Hodásová et al [ 13 ]. They found that the copolymer infiltrated among the ceramic filaments can act as a mechanical stabilizer and adhesion promoter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the investigated process allows for the free fabrication of high-performance components made of a ceramic matrix composite. A polymer–ceramic composite material for dental implant applications capable of withstanding high mechanical stress and wear was proposed and researched by Hodásová et al [ 13 ]. They found that the copolymer infiltrated among the ceramic filaments can act as a mechanical stabilizer and adhesion promoter.…”
Section: Introductionmentioning
confidence: 99%
“…It can be noted that the main research directions in the field of manufacturing parts from ceramic materials with a polymer matrix by 3D printing have focused on aspects related to the physical–mechanical properties of the materials of the parts [ 4 , 5 , 9 , 10 ], improving the manufacturing technologies of such parts [ 6 , 7 , 11 , 12 , 18 , 19 , 20 ], the influence of different factors on the material properties of parts manufactured by 3D printing [ 2 , 8 , 13 , 14 , 15 ], and the identification of new possibilities of using the respective materials [ 3 , 5 , 9 , 10 , 11 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results highlighted that a zirconia-based PICN displayed higher strength than commercial resin composites and PICN. Hodasova et al [10,22] prepared 3D-printable PICNs by combining 3D-printed ZrO 2 with 50% infilled macropores and biocompatible adhesive copolymer for dental implants. These PICNs possessed excellent compression strength with moderate hardness.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent works, we have successfully combined a biocompatible adhesive copolymer with 3D-printed yttria-stabilized tetragonal zirconia scaffolds (3Y-TZP) with 50% infilled macropores 9 to palliate crack propagation in 3D-printed polymer-infiltrated ceramic network (PICN) scaffolds under compression forces. 9 , 10 Moreover, the hybrid materials conserve their biocompatibility, promoting the growth and proliferation of MG-63 osteoblast cells on their surface.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Improvement of 3D-printing techniques has made the design and production fast and easy, providing products of high-end quality. 15−20 The main advantage is that the design of the pore size and distribution can be controlled with CAD/CAM processes and therefore adjusted according to the necessity of the application, 9,10 which is not possible using traditional sintering methods of compact ceramic structures. 21 The PICN sample itself does not apparently promote the growth of bacteria but does not have antimicrobial properties usually desirable in the biomedical field to prevent biofilm formation.…”
Section: Introductionmentioning
confidence: 99%